Application of Umbilical Cord Blood Stem Cells in Regenerative Medicine - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2014)
BACKGROUND: Since the first umbilical cord blood (UCB) transplant, performed 25 years ago, UCB banks have been established worldwide for the collection and cryopreservation of UCB for autologous and allogeneic transplants.CONTENT: Much has been learned in a relatively short time on the properties of UCB hematopoietic progenitors and their clinical application. More interestingly, non-hematopoietic stem cells have been isolated from UCB. These cells can be grown and differentiated into various tissues including bone, cartilage, liver, pancreas, nerve, muscle and so on. The non-hematopoietic stem cells have an advantage over other sources of stem cells, such as embryonic stem cells or induced pluripotent stem cells, because their supply is unlimited, they can be used in autologous or allogeneic situations, they need minimal manipulation and they raise no ethical concerns. Future studies will test the potential of UCB cells for the treatment of several diseases including, among other possibilities, diabetes, arthritis, burns, neurological disorder and myocardial infarction.SUMMARY: In addition to hematopoietic stem cells, UCB contain a large number of non-hematopoietic stem cells. In the absence of ethical concern, the unlimited supply of UCB cells explains the increasing interest of using UCB for developing regenerative medicine.KEYWORDS: UCB, transplantation, UCB bank, HSC, MSC, CD34, CD133, VSEL